CONVERSATION SCRIPTS-BASED VIDEO SHOOTING ACTIVITY IN SUPPORTING THE EFL STUDENTS’ SPEAKING SKILL - Putu Novia Indah Sari; I Ketut Wardana; Ni Luh Putu Dian Sawitri (Academic Journal on English Studies (AJOES), 2022)
This study attempted to investigate whether, and how, the student’s English speaking ability was improved by a conversation script-based video shooting activity. Thus, to achieve the research objective, this study made use of a qualitative approach with a classroom action research design. The teaching activities were run on two cycles, each of which consisted of planning, observation, action, and reflections. Two instruments, a test, were used to measure the effectiveness of the teaching activity, and a questionnaire was used to measure students’ learning intention toward the activity. The results showed that the conversation script-based video shooting activity improved the students’ speaking ability. Furthermore, the activity also motivated and encouraged the students to involve doing conversation. It can be seen from the increasing learning achievement from the mean score of the pre-test was 53.17, the mean score of post-test 1 was 76.53, and the mean score of the final post-test was 83.53. In addition, students revealed positive academic encouragement toward the technique. So, a conversation script-based video shooting activity is suggested to give a practical impact on the students’ speaking skills because it provides equal opportunity for students to perform their English language competence in any roles written in the scripts in daily life context.